THE IMPACT OF SOCIAL MEDIA ON VERBAL COMMUNICATION AMONG UNDERGRADUATES – A CRITICAL PERSPECTIVE - R, Vijayalakshmi (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The development of digitalization and social media in the world has made the lives of people easy. It helped users to get connected with the rest of the world to share information, knowledge, opinions, share views, etc. With the arrival of the covid- 19 pandemic, socializing had been replaced by social media. The government protocol of social distancing, online lifestyle, and online education. Social distancing had resulted in the greater usage of social media platforms like YouTube, Facebook, and Instagram by citizens. But among youngsters, the usage of social media platforms can be observed to a greater extent. Though social media platforms are widely used for entertainment and relaxation at the same time availability of infotainment can be observed by academicians, scholars, and teachers to a greater extent. As the effect covid – 19 teaching and learning methodology from chalk and talk method had completely become virtual. Online learning through social media apps can be seen in greater demand and sharing information through social media had made the work easy. Taking this into consideration the research paper tries to look into the effect of social media teaching on respective platforms of YouTube, Instagram, and Facebook and how far the implementation of social media teaching and learning in regular classes can help the undergraduates to be active in regular offline classes. The study includes both quantitative and qualitative research analysis to draw out the accurate outcome for undergraduate students and to suggest the implementation of social media teaching with an example of a draft lesson plan.